(untitled) (Biological Sciences - PJSIR, 1995)
Seven different mixtures of three, four and five com- pounds randomly selected were prepared for qualitative analy- sis. The same mixtures were prepared using accurately mea- sured amounts for separation and quantitative determination of individual components.